Stability of a Deep Foundation Pit with Hard Surrounding Rocks under Different in-Time Transverse Supporting Conditions - Yang Li; Zhanguo Ma; Furong Gao; Peng Gong; Zhiqun Gong; Kelong Li (Applied Sciences, 2024)
This paper focuses on investigating the stability of a deep foundation pit with hard surrounding rocks at different excavation stages with different supporting schemes by means of numerical calculations. The supporting schemes in question were combinations of one fixed vertical support and four varied transverse supports. Drilled grouting piles were used as vertical supports, and the commonly used steel bracings and prestressed anchorages served as transverse supports. The parameters used to evaluate the stability of the foundation pit at different excavation stages included the lateral displacements of the surrounding rocks, the settlement of the surrounding ground, the axial forces of steel bracings, and displacements at the tops of the drilled grouting piles. Simulation results showed that when a transverse supporting scheme consisting of one-layer steel bracings and prestressed anchorages set at 9 m and 22.5 m underground, respectively, was adopted, the lateral displacements of the surrounding rocks and settlement of the surrounding ground at different excavation stages were the largest compared to those under the other three transverse supporting schemes, while the corresponding values were lower compared to those allowed in Chinese standard GB50007-2011, demonstrating that this kind of supporting scheme is effective in terms of ensuring the safety of the foundation pit at different excavation stages. Moreover, the setting techniques for this kind of supporting scheme were relatively simple, and the corresponding influences of supporting element arrangements on excavation techniques were the lowest. Therefore, one-layer steel bracings and one-layer prestressed anchorages constituted the most suitable transverse supporting scheme for excavating a deep foundation pit with hard surrounding rocks.